Analisis Metode Penyelesaian Relasi Rekursif dalam Matematika Diskrit serta Implikasinya terhadap Pembelajaran - Siregar, Fadilla Sri Utami; Rambe, Arjuna Yahdil Fauza; Amir, Almira (Journal of Natural Sciences, 2025)
Recursive relations are an important concept in discrete mathematics used to define sequences, functions, and computational models. This study aims to analyze various methods for solving recursive relations and their implications for mathematics learning. The study used a library research approach to 15 articles published in SINTA-accredited national journals (1–5) and Scopus-indexed international journals during the 2020–2025 period. Articles were selected through identification, screening, eligibility, and inclusion stages based on topic relevance and full-text availability. The results of the study indicate that each method has its own characteristics: substitution and iteration are suitable for basic cases, characteristic equations are effective in homogeneous linear relations, generating functions excel in combinatorics contexts, and numerical approaches are relevant for complex dynamic systems. From a learning perspective, the application of recursive relations contributes to improving students' critical, logical, and creative thinking skills through discovery learning strategies, blended learning, and the use of concrete media. This study emphasizes the importance of integrating recursive relations in the discrete mathematics curriculum to equip students with higher-order thinking skills that are appropriate to the demands of the 21st century.